2021
DOI: 10.1016/j.ijchp.2021.100251
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal study of preadolescent and adolescent substance use: Within-individual patterns and protective factors

Abstract: Background/Objective Substance use is one of the main risks for adolescent health. Many research projects have studied longitudinal patterns of use and risk/protective factors, but the number of studies focused on within-individual stability and change is low. The objective of this study was to discover specific longitudinal profiles of drug use and explore the role of social and emotional competencies, and empathy as possible protective factors against substance use. Method: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 25 publications
0
3
0
1
Order By: Relevance
“…Our results show that the scores of girls and boys on self-efficacy and coping plans do not differ and thus do not need a more targeted approach. Yet, international and national studies have shown the importance of self-efficacy and coping plans in the prevention of cannabis use in young people [36][37][38]. Thus, it would be recommended to focus the cannabis use prevention presentations on helping adolescents develop action skills and planning how to reject the offer of cannabis use (e.g., through role-play, and simulations), especially in boys, who are the ones who reported having the greatest intention to use in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Our results show that the scores of girls and boys on self-efficacy and coping plans do not differ and thus do not need a more targeted approach. Yet, international and national studies have shown the importance of self-efficacy and coping plans in the prevention of cannabis use in young people [36][37][38]. Thus, it would be recommended to focus the cannabis use prevention presentations on helping adolescents develop action skills and planning how to reject the offer of cannabis use (e.g., through role-play, and simulations), especially in boys, who are the ones who reported having the greatest intention to use in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, families should supervise their adolescent children, so they are not involved in substance use, especially during the pandemic. Although it is not allowed to sell alcohol and tobacco to minors in Spain, substance use in adolescents is common (Rodríguez-Ruiz et al, 2021). Many adolescents reported noncompliance with COVID-19 measures.…”
Section: Discussionmentioning
confidence: 99%
“…Las competencias socioemocionales del alumnado se relacionan con un mayor desarrollo de sus competencias académicas, como la competencia en comunicación lingüística (Llorent, González-Gómez et al, 2020). Además, las competencias socioemocionales protegen a los adolescentes ante conductas antisociales, en el contexto offline y online, tales como consumo de sustancias (Rodríguez-Ruiz et al, 2021), bullying (Coelho y Marchante, 2021;Zych, Beltrán-Catalán et al, 2018), cyberbullying (Eden et al, 2016;Marín-López et al, 2020) y comportamientos violentos en general (Espejo-Siles et al, 2020;Nasaescu et al, 2021).…”
Section: Introductionunclassified